Integrated Safety Analysis on Skin Cancers among Patients with Psoriasis Receiving Ixekizumab in Clinical Trials - Saxon D. Smith; Alexandros Stratigos; Matthias Augustin; Jose Manuel Carrascosa; Susanne Grond; Elisabeth Riedl; Wen Xu; Himanshu Patel; Mark Lebwohl (Dermatology and Therapy, 2023)
Abstract Introduction Limited data exist on skin cancer risk in patients with psoriasis using biologics. Here, we report treatment-emergent adverse events (TEAEs) of skin cancer in patients treated with ixekizumab from psoriasis clinical trials. Methods Integrated safety databases from 17 clinical trials of adults with moderate-to-severe psoriasis treated with ≥ 1 dose of ixekizumab for ≤ 5 years were used to analyze exposure-adjusted incidence rates (IRs) per 100 patient-years of exposure (PYE) and clinically characterize dermatologist-adjudicated skin cancer TEAEs. Results Of 6892 patients, 58 presented with ≥ 1 skin cancer TEAE (IR 0.3) with IRs remaining stable with longer ixekizumab exposure. Non-melanoma skin cancer (NMSC) was the most common event (IR 0.3) affecting 55 patients; of those, 44 had basal cell carcinoma (IR 0.2) and 16 had squamous cell carcinoma (IR 0.1). Two treatment-emergent melanoma events were identified; neither were classified as serious AEs. Conclusions Incidence of skin neoplasms in patients with psoriasis treated with ixekizumab for ≤ 5 years was low, and among those events, NMSC was most common. Limitations included that longer exposure may be required to confirm risk of skin cancer and that the study exclusion criteria of several studies, which excluded patients with skin cancer events within 5 years prior to baseline, might limit interpretation of skin cancer risk in this cohort. These findings support the safety profile of ixekizumab for patients requiring long-term psoriasis control.